Měření spokojenosti zákazníka v oblasti managementu kvality - Plánková, Barbora (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Bakalářská práce pojednává o měření spokojenosti zákazníka v oblasti managementu kvality. Teoretická část se zabývá spokojeností zákazníka a je zde rozebrána metodika jejího měření. Praktická část popisuje aktuální měření spokojenosti zákazníka ve firmě Tawesco s.r.o., Kopřivnice. Cílem je vyhodnotit současný stav a následně doporučit možné opatření pro zlepšení managementu kvality v oblasti spokojenosti zákazníka, což je zpracováno následovně. Práce je především zaměřena na úpravy formální stránky dotazníku, doporučení vztahující se k navýšení odezvy respondentů a zefektivnění procesu dotazování. Veškeré návrhy změn jsou vypracovány na základě rozboru současného firemního dotazníku a zhodnocení dat měření spokojenosti zákazníků z let 2017-2019. Jednotlivá doporučení by měla vést ke zpřesnění informací získaných od respondentů, což by mělo přispět k účinnému zavádění zlepšení a následnému nárustu spokojenosti zákazníka.

The bachelor thesis deals with the measurement of customer satisfaction in the field of quality management. The theoretical part contains customer satisfaction and the methodology of measuring customer satisfaction is analyzed. The practical part describes current measurement of customer satisfaction in the company Tawesco s.r.o., Kopřivnice. The aim of this work is to evaluate the current situation and propose recommendations for improving quality management in the area of customer satisfaction, which is processed as follows. This bachelor thesis is mainly focused on the modification of the formal side of the questionnaire, recommendations for increasing the response rate of respondents and streamlining the survey process. There are developed reccomendations for changes based on the analysis of the current companies questionnaire and comparability of data obtained from respondents from the years 2017-2019. Particular recommendations should lead to more accurate information obtained from customers and it ensures more effective implementation of improvements and subsequent increase of customer satisfaction.
Measurement of customer content of quality management
Keywords: Měření spokojenosti zákazníka; management kvality v oblasti spokojenosti zákazníka; metodika měření spokojenosti zákazníka; rešerše současného stavu; zpětná vazba; dotazníkové šetření; návrh opatření; proces neustálého zlepšování; Measurement of customer satisfaction; quality management in the field of customer satisfaction; the methodology of measuring customer satisfaction; search of the current state; feedback; questionnaire survey; proposal of measures; continuous improvement process